Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Solving systems by substituting Y= -3x+52x+y=6

Sagot :

Answer:

x=-1, y=9.

Explanation:

Given the system of equations

[tex]\begin{gathered} y=-3x+5 \\ 2x+y=6 \end{gathered}[/tex]

Substitute y=-3x+5 into 2x+y=6.

[tex]\begin{gathered} 2x+y=6 \\ 2x+(-3x+5)=6 \\ 2x-3x+5=6 \\ -x=6-5 \\ -x=1 \\ x=-1 \end{gathered}[/tex]

Next, we solve for y.

[tex]\begin{gathered} y=-3x+5 \\ =-3(-1)+5 \\ =4+5 \\ y=9 \end{gathered}[/tex]

The solution to the system of equations are:

x=-1 and y=9.

Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.